2021
DOI: 10.1080/13880209.2021.1942504
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin, a novel food, attenuates acute alcohol-induced liver injury in mice through regulating the NF-κB-mediated inflammation and PI3K/Akt signalling pathways

Abstract: Context: Taxifolin (TAX) has effective anti-inflammatory, antioxidant and hepatoprotective activities, but its potential mechanism has not been revealed. Objective: To evaluate the potential protective effect of TAX on acute alcohol-induced liver injury in mice. Materials and methods: Alcoholic liver injury model was established by oral alcohol in mice, and randomly distributed in five groups (n ¼ 10): Normal group (oral saline only); Alcohol group (concentration of fermented alcohol: 56%, 6 mL/kg); TAX groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…An additional advantage of TA therapy for Cd-intoxicated patients is supported by the research that shows it might diminish inflammation and/or suppress cytokine storms in those individuals exposed to Cd. Furthermore, a recent study demonstrated that TA showed hepatoprotective effects against alcohol-induced hepatic damage via modulating the NF-κB-mediated pro-inflammatory cytokines production and hepatic inflammation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional advantage of TA therapy for Cd-intoxicated patients is supported by the research that shows it might diminish inflammation and/or suppress cytokine storms in those individuals exposed to Cd. Furthermore, a recent study demonstrated that TA showed hepatoprotective effects against alcohol-induced hepatic damage via modulating the NF-κB-mediated pro-inflammatory cytokines production and hepatic inflammation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…TA has also been shown to prevent OS-stimulated retinal pigment epithelium (RPE) cell destruction and apoptosis via activation of Nrf2 and the phase II antioxidant enzyme system. Furthermore, TA ameliorated acute alcohol-stimulated hepatic damage via modulating the NF-κB-mediated inflammation in mice [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of GSH, MDA, and SOD are important indicators reflecting oxidative stress damage ( Ding et al, 2021 ). Therefore, the levels of GSH, MDA and SOD in liver tissue were detected.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] According to previous research, PI3K signaling is involved in a variety of human disorders, such as proliferative disorders and cancers. 6,29,30) Furthermore, the PI3K/AKT/mTOR pathway has been shown to modulate tumor cell autophagy and apoptosis. 31) As a result, inhibiting PI3K signaling has been identified as a potential treatment alternative for these disorders, and PI3K serves as a major target for drug development.…”
Section: Discussionmentioning
confidence: 99%